2004
DOI: 10.1111/j.1742-7843.2004.pto940505.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Cytogenetic Toxicity of Metronidazole in Male Mice

Abstract: The purpose of this study was to examine the effects of metronidazole (500 mg/kg b.wt. daily by gavage for 14 consecutive days) on male fertility, haematopoiesis and genotoxic affinity. Mature male Swiss mice were treated with metronidazole and divided into 3 groups each with 10 animals, examined after 2 weeks, 1 and 2 months from the onset of drug administration. The results demonstrated that metronidazole significantly (PϽ0.05) decreased the weight of the testes, epididymides and accessory sexual organs (sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 29 publications
4
44
1
Order By: Relevance
“…Previous reports indicate that MTZ is genotoxic in mouse somatic cells [el-Nahas and el-Ashmawy, 2004], and that chronic treatment with MTZ is carcinogenic in rodents [Sloan et al, 1983;A-Kareem et al, 1984;Fahrig and Engelke, 1997]. In the present study, relatively shortterm treatment of rats with MTZ increased PMNC frequencies, but the increase was significant only with the highest MTZ dose tested (100 mg/kg), a dose that was greater than MTZ doses that were genotoxic in other assays and greater than human therapeutic doses.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…Previous reports indicate that MTZ is genotoxic in mouse somatic cells [el-Nahas and el-Ashmawy, 2004], and that chronic treatment with MTZ is carcinogenic in rodents [Sloan et al, 1983;A-Kareem et al, 1984;Fahrig and Engelke, 1997]. In the present study, relatively shortterm treatment of rats with MTZ increased PMNC frequencies, but the increase was significant only with the highest MTZ dose tested (100 mg/kg), a dose that was greater than MTZ doses that were genotoxic in other assays and greater than human therapeutic doses.…”
Section: Resultscontrasting
confidence: 67%
“…Previous studies have demonstrated the genotoxicity of MTZ in rodents [Neal and Probst, 1984;Mudry et al, 1994;Fahrig and Engelke, 1997;el-Nahas and el-Ashmawy, 2004]; however, rats have high levels of nitroreductases in their intestinal microflora, especially when compared with humans, and this activity could be responsible for to the genotoxicity of MTZ in rodents when the compound is administered orally [Fahrig and Engelke, 1997]. In the present study, MTZ was administered topically to the rat vagina, so the compound may not have been metabolized in the same way as occurs when MTZ is administered orally or parenterally.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…), undulated tails (und.) and bent trails; c sperms with coiled flagellum (coiled), and sperms with tails with ansa (ansa) genotoxic, cytotoxic, and mutagenic activity on the spermatogonia (El-Nahas and El-Ashmawy, 2004). MTZ results in decreasing testicular and epididymal weights and decreasing testicular spermatid and epididymal sperm counts (McClain et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…However, metronidazole is toxic, causing nausea, vomiting, abdominal pain and other effects. In addition, it might be carcinogenic to patients when used at high doses and/or as a long-term treatment, evidenced by DNA breakages and chromosome aberrations caused by this drug in cultured cells, and by its carcinogenic effects in animal tests (Roe, 1983;Dobias et al, 1994;El-Nahas & El-Ashmawy, 2004;Kapoor et al, 1999;Mudry et al, 1994).…”
Section: Bacterial Species That Infect the Diabetic Footmentioning
confidence: 99%